2014
DOI: 10.1097/hjh.0000000000000061
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and overweight/obesity in Ghanaians and Nigerians living in West Africa and industrialized countries

Abstract: Hypertension and overweight/obesity are highly prevalent conditions in West Africa and in its migrants residing in industrialized countries. Urgent measures are needed to prevent CVD risk factors and halt the clinical sequelae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
62
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 46 publications
(57 reference statements)
8
62
1
Order By: Relevance
“…Female diabetes patients tended to be older than male patients with the difference in mean age attaining statistical significance in 3 out of the 31 years under review. The rising rates of diabetes admissions and increasing mean age of admitted patients is reflective of the increasing longevity of the citizenry of Ghanaians most especially females [23,29,30]. The 28-day in-patient mortality from diabetes admissions of 18.5% observed in this study ranks among the highest in the published literature.…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…Female diabetes patients tended to be older than male patients with the difference in mean age attaining statistical significance in 3 out of the 31 years under review. The rising rates of diabetes admissions and increasing mean age of admitted patients is reflective of the increasing longevity of the citizenry of Ghanaians most especially females [23,29,30]. The 28-day in-patient mortality from diabetes admissions of 18.5% observed in this study ranks among the highest in the published literature.…”
Section: Discussionsupporting
confidence: 50%
“…Overall female gender dominated the number of admitted cases of diabetes in this cohort. This is largely explained by the higher prevalence of obesity and physical inactivity among women [21][22][23][24]. Additionally, women live relatively longer than men and as a result are exposed to diabetes and other non-communicable diseases [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Framingham Heart Study and other landmark studies2, 3, 4 have demonstrated that CVD risk factors—smoking, obesity, hypertension, hyperlipidemia, physical inactivity, and diabetes mellitus—synergistically increase CVD risk and death. Likewise, in sub‐Saharan Africa, CVD is becoming a leading cause of morbidity and mortality because of the increasing prevalence of CVD risk factors attributed to the “epidemiological transition,” characterized by shifts in disease and mortality patterns from infectious diseases to noncommunicable diseases as major causes of morbidity and mortality 5, 6…”
Section: Introductionmentioning
confidence: 99%